Chinatown compromised? - Chua, Lynette Hua Ting. (2008)
In recent years, there has been rising awareness of conservation efforts. The Singapore Tourism Board (STB) and the Urban Redevelopment Board are the two authorities that have been actively involved in local conservation efforts. We have applied Cost Benefit Analysis to evaluate the effects of the earlier conservation work carried out in Kreta Ayer during the 1980s. The results obtained show that the economic benefits reaped from conservation have outweighed the costs involved in the project.